1997
DOI: 10.1080/02724936.1997.11747893
|View full text |Cite
|
Sign up to set email alerts
|

Childhood goitre in Saudi Arabia

Abstract: Thirty-two Saudi children (aged 1.5-14 years) with goitre were seen over a 6.5-year period in a paediatric endocrinology clinic. There was a female to male ratio of 1.9:1. Of these, 27 (84.3%) had diffuse thyroid enlargement and five (15.7%) nodular goitre. The commonest causes were dyshormonogenesis (37.5%) followed by Hashimoto's thyroiditis (34.4%). Three boys and one girl had Graves' disease. There were three (9.4%) with simple goitre and one case each of iodine deficiency goitre and tuberculous thyroiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…In the Kingdom of Saudi Arabia (KSA), thyroid disorders are common among the general population at the different ages [18][19][20][21] and goitre was frequently reported in Saudi children, particularly among those who were living in high altitude areas of the kingdom [22,23]. Alissa et al (2009) followed the WHO recommended median UIC cut-off values for iodine adequacy, and their results revealed severe deficiency in their enrolled hypothyroid patients as well as healthy participants from the Western region of KSA [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the Kingdom of Saudi Arabia (KSA), thyroid disorders are common among the general population at the different ages [18][19][20][21] and goitre was frequently reported in Saudi children, particularly among those who were living in high altitude areas of the kingdom [22,23]. Alissa et al (2009) followed the WHO recommended median UIC cut-off values for iodine adequacy, and their results revealed severe deficiency in their enrolled hypothyroid patients as well as healthy participants from the Western region of KSA [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the Kingdom of Saudi Arabia (KSA), thyroid disorders are common among the general population at the different ages [18][19][20][21] and goitre was frequently reported in Saudi children, particularly among those who were living in high altitude areas of the kingdom [22,23]. Alissa et al (2009) followed the WHO recommended median UIC cut-off values for iodine adequacy, and their results revealed severe deficiency in the enrolled hypothyroid patients as well as healthy participants from the Western region of KSA [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the Kingdom of Saudi Arabia (KSA), thyroid disorders are frequent among the general population at different ages [17][18][19][20]. Goitre was also found to be common in Saudi children especially in those living in high altitude areas of the kingdom [21,22]. Alissa et al (2009) reported iodine deficiency in 85% and 83% of their healthy participants and hypothyroid patients from the Western region of KSA, respectively [23].…”
Section: Introductionmentioning
confidence: 99%